Outcasts united : the story of a refugee soccer team that changed a town - St. John, Warren (Ember, 2013)
American-educated Jordanian Luma Mufleh founds a youth soccer team comprised of children from Liberia, Iraq, Afghanistan, and the Balkan states, and elsewhere in the refugee settlement town of Clarkston, Georgia, bringing the children together to discover their common bonds as they adjust to life in a new homeland.